Podocytes … What’s Under Yours? (Podocytes and Foot Processes and How They Change in Nephropathy) - Neal, Chris R. (Frontiers in Endocrinology, 2015)
Most of the described structure of podocytes in health and disease has been inferred from light and electron microscopic studies of rodent models. The variation in filtration barrier features are measured on micrographs, the aim being statistical significance. Such is the technical campaign waged against kidney disease but this approach can be misleading. The signalling cascades and connectivity of the podocyte and foot processes are inferred from in vitro studies that at best blurr the reality of the in vivo state. This review will outline actin signalling connectivity and the key differences in the structural and functional domains squeezed into the foot processes (FP) and the relationship of these domains to other parts of the podocyte. It covers the changes in podocytes during nephropathy concentrating on FP and finally proposes an alternative interpretation of FP ultrastructure derived from articles published over the last 60 years.